Approaches to Assessing the Innovative Potential of Territorial Social-Economic Systems - VOLCHKOVA, Irina V.; VOTYAKOVA, Irina V.; NEDOSPASOVA, Olga P.; VOROBYEVA, Ekaterina S.; NEDOSPASOV, Anatoly A. (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
This study provides an insight into some of the theoretical and practical aspects of putting together a methodological approach to assessing the innovative potential of territorial social-economic systems. It owes its relevance to the lack of an up-to-date methodological framework for the study of the innovative potential of varied-level territorial social-economic systems – municipal units, in particular. The content of this scholarly issue is grounded in the need to reconsider and complement the theoretical-methodological foundations and methodological tenets of research into innovative potential. In this regard, the purpose of this study is to systematize methodological approaches to assessing the innovative potential of territorial social-economic systems. The study represents the authors’ construal of the essence of innovative potential. It examines existing foreign and domestic methodological approaches to assessing the innovative potential of varied-level territorial social-economic systems; identifies some of the critical issues in the process of putting together a methodological approach to assessing innovative potential. The paper draws the conclusion that the results obtained as a result of this study are intended to complement existing notions of the essential-substantive characteristic of the innovative potential of social-economic systems and approaches to assessing it. Even so, the scholarly focus area in question may still require not just conducting further research into its theoretical aspects but also working out relevant research-to-practice recommendations on the effective use of the innovative potential of regions and municipal units. The study employs empirical methods (comparison and observation), methods of comparative-analytical analysis, the expert assessment method, and methods of correlation-regression analysis.